Lone mothers with low income face obstacles to practice their mothering (Sociologisk Forskning, 2017)
Sweden stands out as a forerunner in the development of gender equality and family dynamics. To deepen the knowledge on power distribution and gender dynamics of couple relations, we investigate how women and men’s childbearing intentions influence actual childbearing behavior. The Young Adult Panel Study (YAPS) has information on both partners’ childbearing intentions in 2009, which we follow for five years with register data on childbearing. The results indicate that women’s childbearing intentions are more important than men’s intentions in determining actual childbirths.